PENEGAKAN HAK DAN KEPASTIAN HUKUM DALAM PROSES PENAHANAN SERTA PENGELUARAN TAHANAN DI INDONESIA - Pakpahan, Novritsar Hasitongan; Putra, Arif Rachman; Darmawan, Didit; Khayru, Rafadi Khan; Kusuma, Galih Satria Alit Widi (Gapenas Publisher, 2025)
The detention and release of detainees is an essential part of Indonesia's criminal justice system that demands a balance between law enforcement and human rights protection. Although Law No. 8 of 1981 concerning the Criminal Procedure Law (KUHAP) has provided a normative basis for detention procedures, the phenomenon of detention without legal procedures and the release of prisoners that do not comply with administrative standards is still often found in practice. Weak supervision, confusion of legal interpretation, and disharmony between technical regulations at the police, correctional and judicial levels have led to violations of prisoners' rights. This study uses a normative juridical approach to examine the effectiveness of the implementation of detention rules and detainee releases, as well as identify the factors causing deviations from the principles of due process of law. The findings suggest that there is an urgent need to tighten standard procedures, strengthen oversight, improve interagency coordination, and provide legal education to stakeholders. Reforms in the governance of detention and detention release are urgently needed to ensure justice and legal certainty, as well as to create a national criminal justice system that is more effective, transparent, and upholds human rights